Preliminary Investigation of the Reliability and Validity of the Clinical Perfectionism Questionnaire in a Clinical Sample. Issue 3 (5th July 2016) - Hoiles, Kimberley J.; Kane, Robert T.; Watson, Hunna J.; Rees, Clare S.; Egan, Sarah J.
Abstract : Perfectionism is a risk and maintaining factor across psychopathology and has been proposed to be a transdiagnostic process. The aim of this study was to examine the reliability and validity of the Clinical Perfectionism Questionnaire (CPQ) in 32 adults (75% female, M age = 35.54 years, SD = 9.71) with a range of psychological disorders, presenting for treatment of clinical perfectionism. There was evidence that the CPQ was correlated with established measures of perfectionism and theoretically related constructs including self-criticism and dichotomous thinking. The CPQ was also able to predict treatment outcome. The internal consistency was not adequate in the current study; however, the sample size was small. Future studies should examine the psychometric properties of the CPQ in a larger sample of individuals with a range of psychological disorders.